The Contribution of Leadership and Supervision of the School Principal to the Work Discipline of Elementary School Teachers in Cluster I Lubuk Basung District, Agam Regency - Melki Evendi; Hanif Alkadri; Nelitawati Nelitawati; Anisah Anisah (Green Publisher Indonesia, 2024)
This research is based on the observations of the researcher at the Public Elementary Schools in Lubuk Basung Subdistrict, Agam Regency, which showed the low performance of teachers. There are many factors influencing teacher performance, including school leadership and school climate. The objectives of this research are to examine: (1) the contribution of school principal leadership to the performance of teachers in Public Elementary Schools in Lubuk Basung Subdistrict, Agam Regency, (2) the contribution of Academic Supervision to the performance of teachers, and (3) the contribution of school principal leadership and Supervision to the performance of teachers. This research uses a quantitative research method with a population of 292 teachers. The sample was taken using proportional stratified random sampling method, totaling 67 teachers. The instrument in this research uses a questionnaire. The results of data analysis show that: (1) school principal leadership significantly contributes to the performance of teachers in Public Elementary Schools in Lubuk Basung Subdistrict, Agam Regency, by 93.2%. (2) Academic Supervision significantly contributes to the performance of teachers, by 50%. (3) School principal leadership and Academic Supervision significantly contribute to the performance of teachers, by 5%. it can be concluded that the hypothesis can be empirically accepted, and the variables of school principal leadership and Academic Supervision are two factors that contribute to the performance of teachers in Public Elementary Schools in Lubuk Basung Subdistrict, Agam Regency, while the remaining 50% is influenced by other variables.